Development and validation of a composite digital balance score for spinocerebellar ataxia: a prospective study - McNames, James; Shah, Vrutangkumar V; Casey, Hannah L; Sowalsky, Kristen L; El-Gohary, Mahmoud; Safarpour, Delaram; Carlson-Kuhta, Patricia; Schmahmann, Jeremy D; Rosenthal, Liana S; Perlman, Susan; Rodríguez-Labrada, Roberto; Velázquez-Pérez, Luis; et al. (The Lancet. Digital health, 2025)
Clinical trials in spinocerebellar ataxia are currently limited by the large sample sizes required by available clinical endpoints. We aimed to devise a digital composite measure of standing and walking balance using wearable inertial sensors that would require smaller sample sizes. The new score is called the Score of Integrated Balance in Ataxia (SIBA). In this study, we developed the SIBA based on a retrospective sample of adults (aged 18–75 years) with spinocerebellar ataxia types 1, 2, 3, or 6, recruited during clinical visits at five sites (four in the USA and one in Cuba) between June 23, 2017, and Aug 21, 2024. Participants were included if they had genetic confirmation of spinocerebellar ataxia, and were able to provide consent, walk 10 m independently without an assistive device, and stand unassisted for 30 s. A cohort of age-specific and sex-matched healthy controls were recruited from family members of the patients. To validate the SIBA, an independent sample of individuals with the same types of ataxias were recruited along with age-matched and sex-matched healthy controls from five centres in the USA (NCT04268147) between June 1, 2019, and April 30, 2024. We performed balance and gait assessments using six wearable sensors (Opal inertial measurement units, APDM Precision Motion, Clario, Portland, OR, USA) on the dorsum of each foot and hand, on the sternum, and on the lower lumbar (trunk) vertebral segments. We used the data from this assessment to develop a composite score from walking at a natural pace for 2 min and standing with feet together and apart for 30 s. We used a multiple criteria decision analysis to weight the relative importance of criteria to guide development of the score. The criteria represented the ability to distinguish groups with known differences, construct validity, reliability, progression, meaningfulness, and concurrent validity. The final composite score integrated two dynamic balance variables from gait (variability of toe-out and double-support time proportion of the gait cycle) and two static balance variables from stance (sway angle root mean square with normal stance width and sway acceleration root mean square with feet together). We compared the SIBA to the Scale for the Assessment and Rating of Ataxia (SARA) for reliability, the ability to distinguish between groups with known differences, construct validity, convergent validity, and the ability to track disease progression. We included 258 individuals (131 females and 127 males) with spinocerebellar ataxia types 1, 2, 3, or 6 (40 premanifest and 218 ataxic) and 100 healthy controls (45 females and 55 males) in the development study; and 53 individuals (27 females and 26 males) with spinocerebellar ataxia types 1, 2, 3, or 6 and 24 healthy controls (14 females and 10 males) in the validation study. The SIBA showed concurrent validity with the SARA (r=0·736). The SIBA was also reliable (test–retest reliability; intraclass correlation coefficient=0·970), could distinguish between participants and healthy controls (area under the receiver operating characteristic curve [AUROC]=0·956), and related to fall risk (AUROC=0·760) in a validation cohort of ambulatory participants with spinocerebellar ataxia, independent from the larger, score-development cohort. Progression of ataxia over 1 year had an effect size five times larger than the SARA score (0·59 vs 0·11). Based on these estimates, clinical trials using the SIBA would require 88% fewer participants than SARA (171 vs 1491) to detect a 50% reduction in the rate of 1-year progression. SIBA is a suitable digital measure of static and dynamic balance for the most common spinocerebellar ataxias in clinical trials. It may permit clinical trials to be completed more rapidly and with fewer participants. Future trials on responsiveness of the SIBA to interventions are needed in larger cohorts. Biogen, Clario, Pfizer, and the Alexander von Humboldt Foundation.